Analisis Strategi PAC (Perhitungan Area Coverage) Dalam Mengukur Daily Income Ekspansi Minimarket Retail Studi Kasus Indomaret - Muh. Junelghy Imran; Jumawan Jasman (Politeknik Ganesha Medan, 2023)
In the right location in a retail minimarket business, there are still many who use the method with a cursory condition of location conditions which can result in inappropriate targets because they do not consider the risk factors that occur at the location. Therefore, it is necessary to build a strategic system in making the decision to establish a retail minimarket using the observation and documentation method by means of PAC analysis (potential coverage area) where this model makes an assessment by surveying the location using the technique of calculating residential potential, calculating potential flows, calculating crowds of public facilities. , observing the socio-economic conditions of the community. In calculating the potential for residential areas with the help of a computer/laptop with the help of the Google Earth (KMZ) satellite, calculating traffic potential using video capture techniques using the timestime application on a cellphone, calculating the potential for public facilities by conducting interviews with employees regarding the number of employees, analyzing the level of crowding of public facilities by counting the number of visitors, and analyzing the socio-economic level of the community by collecting data at the regional statistical center. So the purpose of the PAC calculation is to measure the estimated daily income